Self-Esteem and Narcissism Tendency among Instagram User Students - Deo, Wihelmina Regha; Damayanti, Yeni; Panis, Marleny Purnamasari; Lerik, Mariana Dinah Ch. (Journal of Health and Behavioral Science, 2025)
Instagram is a popular social media platform among teenagers and students. Its interesting features make users able to exist and show their abilities, beauty, or other unique things. However, if excessive, this can become a form of narcissism, one of which is influenced by self-esteem. This study examines the relationship between self-esteem and narcissistic tendencies in 221 Instagram user students from the Psychology Study Program at Nusa Cendana University, Kupang. Data were collected using the self-esteem scale and the narcissism tendency scale, based on Coopersmith's theory and Raskin and Terry. The purposive sampling method was used for sampling from a population of 521 students. Spearman correlation analysis showed a significant positive relationship (r = 0.246, p = 0.000), which means that the higher the self-esteem, the higher the narcissistic tendencies in college students who use Instagram. This finding confirms that self-esteem plays a role in influencing narcissistic behavior on social media.